2016
DOI: 10.1088/1054-660x/26/12/126101
|View full text |Cite
|
Sign up to set email alerts
|

Laser wavelength effect on nanosecond laser light reflection in ablation of metals

Abstract: Reflection of nanosecond laser pulses with different wavelengths (1.06 and 0.69 µm) in ablation of titanium in air is studied experimentally. The laser wavelength effect on reflection is essential at low laser fluence values. However, it becomes negligible for laser fluence values by about an order of magnitude higher than the plasma ignition threshold. We speculate that the disappearance of the wavelength effect is explained by counteracting processes of the laser light absorption in plasma, which increases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Hence, the target reflectivity or roughness of the pristine target surface seems to be less‐relevant in the high‐fluence regime where the cavitation bubble volumes are comparable for all materials except Al. This observation is further supported by Bevanides et al., who showed that the reflectivity drops significantly during ns‐ablation when the laser fluence is much higher than the ablation threshold [84] …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Hence, the target reflectivity or roughness of the pristine target surface seems to be less‐relevant in the high‐fluence regime where the cavitation bubble volumes are comparable for all materials except Al. This observation is further supported by Bevanides et al., who showed that the reflectivity drops significantly during ns‐ablation when the laser fluence is much higher than the ablation threshold [84] …”
Section: Resultssupporting
confidence: 63%
“…However,r ecent studies have shown that the bulk material's reflectivity is of minor importance when the target is ablated with laser fluences far above the ablation threshold. [72,84] Since the incident laser fluence of 166 Jcm À2 used for ablation is two orders of magnitude higher than the ablation threshold (see Ta ble 1), it is concluded that differences in surface roughness can be neglected for the discussion of the SEM images. Nevertheless, the surface roughness is important concerning incubation effects at lower incident laser fluences, discussed in more detail in the cavitation bubble section of this work.…”
Section: Resultsmentioning
confidence: 99%
“…With increasing pulse energy the ignited plasma becomes the driving force for the cavitation bubble as already discussed above. On the other hand, the reflectivity drops for laser ablation with nanosecond pulse duration when the fluence is far above the plasma threshold . This reduces both the energy loss and the incubation effects due to the reflectivity change induced by the roughness.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the reflectivity drops for laser ablation with nanosecond pulse duration when the fluence is far above the plasma threshold. [39] This reduces both the energy loss and the incubation effects due to the reflectivity change induced by the roughness. As shown in Figure 2a) right hand side, the first bubble induced at 10 mJ pulse energy is very similar for the Ag, Au and Ge target.…”
Section: Target Incubation and Bubble Formation At High Fluencementioning
confidence: 99%
“…Affecting of powerful laser irradiation on metallic (dielectric and semiconductor) targets leads to formation of craters and holes, moving away of substance from a target -to the ablation [1][2][3][4][5][6][7][8][9][10][11][12]. The special role are here playing the different thermodynamic states -"solid, liquid, gas, plasma" in which substance consistently goes across.…”
Section: Introductionmentioning
confidence: 99%